The effect of using cognitive modeling in developing reflective thinking skills and the trend towards science for eighth grade female students in Erbil (Journal of the College of Basic Education, 2022)
The current research aims at investigating (the effect of using cognitive modeling on developing thinking skills. Reflective trend among students of the eight grade in Erbil ), and to verify the objectives and hypotheses of the research ,the sample of the study were taming the students of Zahra Preparatory School for the academic year 2019-2020 . They have been selected as the research sample. The sample consists of (60) students. They were randomly distributed over two groups, the experimental and the control groups who studied via the traditional methods. After the equalizing the two groups according to the variables of age and intelligence, and the pre-application of the measure of the contemplative thinking skills, and by the pre- application to measure the trend towards the subject of science . To achieve the objectives and the hypotheses, the researcher selected the requirements of the study for each of the measures of contemplative skills, which consists of 30 paragraphs, .She also prepared the measure trend for the science module, which also consists of 30 paragraphs After confirming the validity and reliability of these paragraphs, they had been utilized for 7 academic weeks then the application of the post test was carried out. The results showed a statistician significant difference at the level of significance (0.05) between the average scores of the experimental group and the average scores of the control group in the post application in the scale of meditative thinking skills as a whole. The results also revealed that there is statistically significant difference at the level of (0.05) between the average scores of the experimental group students and the average scores of the control group in the post application and in the measure of the trend towards science, and the presence of statistically significant differences at the level of (0.05) between the mean scores of the experimental group In the measure of reflective thinking skills (pre and posttest) in each of the dimensions reflective) observation , detecting fallacies , giving convincing explanation, reaching conclusions and suggesting convincing solutions), as well as the presence of statistically significant differences at the level of (0.05) between the average scores of the experimental group students in the test. The trend towards science (pre and posttest), and the research ended with a set of recommendations related to the research results.